Aerobic exercise lengthens telomeres and reduces stress in family caregivers: A randomized controlled trial - Curt Richter Award Paper 2018. (December 2018) - Puterman, Eli; Weiss, Jordan; Lin, Jue; Schilf, Samantha; Slusher, Aaron L.; Johansen, Kirsten L.; Epel, Elissa S.
Highlights: Caregivers who became physically active significantly lengthened in average telomere lengths compared to those in waitlist. Caregivers who became physically active also improved in their cardiorespiratory fitness, BMI, and perceived chronic stress. However, caregivers in either group didn't change in their telomerase activity levels. Abstract: Study design: Family members caring for chronically ill relatives are typically sedentary, chronically stressed, and at high risk of disease. Observational reports suggest caregivers have accelerated cellular aging as indicated by shorter leukocyte telomere lengths. We performed a randomized controlled trial to examine the effect of aerobic exercise on changes in telomerase levels (primary outcome) and telomere lengths (secondary outcome) in inactive caregivers. Methods: 68 female and male community dwelling dementia caregivers who reported high stress and physical inactivity were randomly assigned to a highly supervised aerobic exercise intervention vs. waitlist control group for 24 weeks. Average leukocyte telomere lengths and peripheral blood mononuclear cells' telomerase activity were measured pre- and post-intervention. All staff completing blood draws, fitness testing and bioassays were blinded to group assignment. Results: The intervention group completed approximately 40 min of aerobic exercise 3–5 times per week, verified by actigraphy. There was high (81%) adherence to 120 min/week of aerobic exercise. Groups did not significantly differ in telomerase activity changes across time, but had significant different telomere length changes across time (67.3 base pairs, 95%CI 3.1, 131.5). There were also significant reductions in body mass index and perceived stress and an increase in cardiorespiratory fitness (i.e., VO2peak ) in the exercising caregivers versus controls. Conclusion: In the context of a highly controlled intervention, exercise can induce apparent telomere lengthening, though the mechanisms remain elusive. Our study underscores the importance of increasing participation in aerobic exercise to improve markers of health and attenuate cellular aging in high-risk samples.